2015
DOI: 10.1074/jbc.m114.636159
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Fungal 1,8-Cineole Synthase from Hypoxylon sp. with Specificity Determinants in Common with the Plant Synthases

Abstract: Background: 1,8-Cineole, a commercially important monoterpene, was identified as a fungal product. Results: The 1,8-cineole synthase was identified from a Hypoxylon fungal genome, and mutagenesis revealed a critical asparagine residue. Conclusion:The fungal 1,8-cineole synthase uses a mechanism similar to the plant version. Significance: This is the first identified fungal monoterpene synthase and may facilitate future terpene synthase identification and production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 82 publications
2
83
1
Order By: Relevance
“…This most important monoterpene is produced through extraction from peppermint oil as well as through some synthetic routes (Bedoukian 1986;Bauer et al 1997). Among the terpenes, fungi usually produce sesquiterpenes; however, recently a prized monoterpenoid, 1,8-cineole was found having been produced by several Hypoxylon/Nodulisporium species (Tomsheck et al 2010;Riyaz-Ul-Hassan et al 2013;Shaw et al 2015). There is also a previous report of isolation of menthol from a fungus, Phomopsis amygdale (Sassa et al 2003).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This most important monoterpene is produced through extraction from peppermint oil as well as through some synthetic routes (Bedoukian 1986;Bauer et al 1997). Among the terpenes, fungi usually produce sesquiterpenes; however, recently a prized monoterpenoid, 1,8-cineole was found having been produced by several Hypoxylon/Nodulisporium species (Tomsheck et al 2010;Riyaz-Ul-Hassan et al 2013;Shaw et al 2015). There is also a previous report of isolation of menthol from a fungus, Phomopsis amygdale (Sassa et al 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Very recently, the first monoterpene synthase genes were identified in the cineoleproducing Hypoxylon sp. which were distinct from the plant homologues but used the same mechanism (Shaw et al 2015). Earlier reports also suggest that there is only limited sequence similarity between plant and microbial enzymes/genes (Starks et al 1997;Yang et al 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(CS Hyp3 ) (Shaw et al, 2015), and they both have been reported to produce 1,8-cineole as their main product. The cineole synthases were cloned into the 1P system (See Figure 1b), and the resulting plasmids (JBEI-15048 or JBEI-15049) were transformed into DH1 cells and tested for production in EZ rich defined media with 1% glucose.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…Monoterpene production in E. coli was achieved by heterologously expressing a nine-enzyme mevalonate pathway organized in three operons expressed in a single plasmid (See 1P system in Figure 1b); this arrangement has been shown to result in high production of limonene (Alonso-Gutierrez et al, 2013 Kampranis et al, 2007;Lis-Balchin, 2002;Nakano et al, 2011;Shaw et al, 2015). In this study we tested two cineole synthases (CSs); one from the bacterium Streptomyces clavuligerus (CS Str ) (Nakano et al, 2011) and the other from the fungus Hypoxylon sp.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%